A prospective study for the assessment of thyroid function by pre and post supervised exercise protocol in newly diagnosed patients of subclinical hypothyroidism - Jhavar, Dharmendra; Patel, Naresh K.; Pandey, V. P. (International Journal of Advances in Medicine, 2019)
Background: The presence of raised serum TSH with serum free T4 and T3 within the reference range falls in subclinical hypothyroidism. It is a well-known fact that exercise affects the activity of thyroid glands and the production of their hormones. Author studied the effect of regular exercise in patients of newly diagnosed subclinical hypothyroidism. Pre and post-exercise thyroid function tests were evaluated to decide about the necessity to start thyroid replacement therapy or to adopt wait and watch policy. Methods: Study enrolled 100 newly diagnosed subclinical hypothyroidism patients attending this tertiary care hospital and randomised them in two groups, one group was subjected to regular physical exercise of 45-60 minutes daily along with supervised treadmill exercise stage 0 for 45-60 minutes once weekly followed by re-evaluation of thyroid function test after 30 days and second group was re-evaluated for thyroid function test without exercise after 30 days. Results: Thyroid profile parameters were compared and analysed by paired ‘t’ test, statistically significant increase in serum T3 (p value <0.05) and serum T4 (p value <0.05), along with significant reduction in TSH level (p value <0.05) were found in exercise group, while in non-exercise group changes in thyroid profile parameters were statistically not significant. There was significant reduction in mean weight in exercise group (p value <0.05), while in non-exercise group changes in weight were not significant. Conclusions: Present study concluded that regular physical exercise can improve thyroid function in patients of newly diagnosed subclinical hypothyroidism and convert them to euthyroid state.